Effects of integrative neuromuscular training on physical fitness and sport-specific performance in football players: a systematic review and meta-analysis - Zhang, Xinrui; Soh, Kim G.; Chan, Yoke M.; Rong, Wenchao; Zhao, Yue; Wang, Xinzhi (SAGE Publications, 2026)
Background: Integrative neuromuscular training (INT) is increasingly incorporated into football conditioning programs to improve neuromuscular function and athletic performance. However, its overall effectiveness across various aspects of physical fitness and sport-specific skills remains unclear. Objective: To systematically review and meta-analyze the effects of INT on physical fitness and football-specific performance outcomes in football players. Methods: Following PRISMA guidelines, this review was prospectively registered in PROSPERO (CRD420251052631). Comprehensive research was conducted in Web of Science, PubMed, SCOPUS, Embase, and CNKI up to May 2025. Methodological quality was evaluated using the TESTEX and ROB 2 tools, while the GRADE framework assessed evidence certainty. Where appropriate, random-effects model meta-analyses were applied. Results: Twelve randomized controlled trials involving 276 football players of varying ages and competitive levels were included. INT produced significant improvements in lower-limb muscle strength (ES = 1.065; p < 0.001), power (ES = 0.453; p < 0.001), sprint speed (ES = −0.341; p = 0.001), agility (ES = −0.398; p < 0.001), balance (ES = −0.897; p < 0.001), and dribbling performance (ES = −1.028; p < 0.05). In contrast, shooting performance showed no significant improvement (ES = 0.324; p = 0.181). Notably, all effect estimates were supported by low-certainty evidence according to the GRADE assessment. Conclusion: INT may be associated with small-to-moderate improvements in strength, sprint speed, power, agility, balance, and dribbling compared with regular training; however, these findings are supported by low-certainty evidence and should be interpreted with caution. Future high-quality studies with standardized protocols are warranted to clarify its impact on advanced technical skills and optimize its integration into football training programs.